Comparison of sagittal spinopelvic alignment in Chinese adolescents with and without idiopathic thoracic scoliosis - Yong, Qiu; Zhen, Liu; Zezhang, Zhu; Bangping, Qian; Feng, Zhu; Tao, Wu; Jun, Jiang; Xu, Sun; Xusheng, Qiu; Weiwei, Ma; Weijun, Wang (Spine (Philadelphia, Pa. 1976), 2012)
A retrospective radiographical study investigated the sagittal alignment in healthy Chinese girls and Chinese girls with idiopathic thoracic scoliosis (T-AIS). To evaluate the sagittal alignment of the pelvis and spine in Chinese girls with idiopathic scoliosis and healthy girls and to assess whether the pelvic morphology differed between white and Chinese girls with AIS. It has been shown that patients with AIS have an abnormal spinopelvic balance and pelvic morphology. Race is a determinant factor of sagittal spinal alignment and serves as a reminder when planning surgical reconstruction for spinal deformity. Until now, there have been no studies documenting the sagittal lumbosacral spine morphology in Chinese girls with T-AIS. In this study, 95 patients with T-AIS and 33 healthy age-matched adolescents were recruited consecutively. Sagittal spinal and pelvic parameters were measured from the standing lateral radiograph, including thoracic kyphosis (TK), lumbar lordosis (LL), upper arc of LL, lower arc of LL, pelvic incidence (PI), sacrum slope (SS), and pelvic tilt (PT). Analysis of variance was used in the comparison of each dependent variable between patients with AIS and healthy adolescents. The relations between all parameters were determined via Pearson correlation coefficient (r). For all the sagittal parameters, only the TK and the upper arc of the LL showed significant differences between girls with AIS and healthy girls. The LL, lower arc of the LL, and 3 pelvic parameters were similar for both groups. The TK was found to be strongly correlated with LL and the upper arc of the LL in both groups. However, the TK was not related to the lower arc of the LL, nor were the 3 pelvic parameters in either group. In addition, LL was found to be associated with PI and SS in both groups. The lower arc of the LL was also correlated with PI for both groups. The PI was related to PT and SS in both groups; however, no correlation was found between PT and SS. In this study, the TK (15.7°), SS (35.1°), and PI (44.2°) were found to be significantly lower in Chinese patients with T-AIS than the values reported in the AIS cohort. In our study, the Chinese girls with T-AIS had similar PI, PT, and SS values when compared with the age-matched healthy girls. There were significant differences in pelvic morphology between Chinese and white girls with AIS. These results suggest that race may influence an individual's spinopelvic morphology. Although we have shown that the TK could affect LL through the upper arc of the LL directly, the evaluation of the thoracolumbar morphology of T-AIS before surgery is important for surgical planning.